Social Support for Parents of Children with Disabilities: A Scoping Review - Rahayu Budi Utami; Puji Astutik (Universitas STRADA Indonesia, 2026)
Background: Raising children with disabilities can be a heavy burden for families which ultimately has a negative impact on the child. Many studies recommend the need for social support for parents. Although the need for social support has been widely reported, the impact of social support for parents with disabilities children in the literature is very diverse. Purpose: This study aims to map and synthesize the existing evidence on the impact of social support for parents of children with disabilities, particularly in identifying its effects on parents, families, and children, as well as to provide a comprehensive understanding that can inform future interventions and support strategies. Methods: Therefore, a scoping review was conducted to identify the impact of social support for parents of children with special needs in international studies. A comprehensive search strategy was employed across multiple electronic databases, including PubMed, Taylor and Francis, Wiley Online library, dan Google Scholar. Results: The database search identified a total of 423 potentially relevant articles. After screening titles and abstracts, 28 potentially relevant articles were identified. All 28 articles were assessed at full-text level, resulting in 10 relevant articles for analysisTen studies were included in the review, from which positive impacts of social support for parents with disability children were identified on parents themselves, families, and children. The positive impacts of social support on parents were increasing resilience, coping skill, parenting efficacy, parenting mental health literacy and decreasing psychological distress and depression-anxiety symptoms. The impacts for parents are also buffering effect on parenteral stress-depression, parenteral stress-efficacy and parents’ satisfaction, positive affect, and depression. The positive impacts on the family increasing family psychological health and family quality of life, and decreasing family burden. Social support is also buffering the effect on family burden-psychological health and resilience. The positive impacts on children are decreasing the emotional and behavioural problem, Conclusion: Social support for parents of children with disabilities has many positive impacts on the parents themselves, the family, and the child. Through identifying the benefits of social support, direction can be provided for interventions by enabling professionals to detect and address available social support.